Efektivitas Pemberian Hipnoterapi dalam Meningkatkan Rasa Percaya Diri Pada Mahasiswa FIK Ibrahimy Sukorejo Situbondo - Neny Yuli Susanti; Eliyawati (BIOMARAS : Journal of Life Science and Technology, 2024)
Hypnotherapy is a very effective method to overcome problems and problems to students who are currently continuing hypnotherapy education is a very easy way so that feelings, thoughts, actions and behaviors can synchronize thoughts. The goal of Hypnotherapy is to hold Kendari to human beings, especially in the human subconscious and hypnotherapy plays a very important role in fostering a sense of self-confidence, a sense of security and comfort in a student at the Faculty of Health Sciences The problem in this study: How is the effectiveness of hypnotherapy in increasing self-confidence in FIK Ibrahimy students so that they are able to be confident and able to speak in public without any nervousness and anxiety. The purpose of this study is how to understand hypnotherapy therapy to foster self-confidence in FIK Ibrahimy studentsand how to know the effectiveness of the results of hypnotherapy lecturers in teachers in increasing self-confidence in FIK Ibrahimy students. This type of research is qualitative research. Qualitative method is field research, which is a research conducted in the actual field. With data types and sources using primary and secondary data. The data analysis that the author uses is analysis Qualitative is inductive, namely an analysis based on the data obtained, then a certain pattern of relationships is developed. The method in conducting respondents was 30 FIK Ibrahimy students who lacked self-confidence and 4 homeroom teachers for the Pharmacy study program and 4 homeroom teachers for the midwifery study program. The conclusion of this study is that hypnotherapy is done well, gradually from discussion, dialogue, comprehension tests, relaxation and active reactions of students Fik Ibrahimy, as well as a good evaluation by the executive lecturer and 4 homeroom teachers in assisting. The results of the calculation with the effectiveness formula showed effectiveness 5 as evidenced by the target of 30 Fik Ibrahimy students who lacked confidence in successfully ouputing 30 Fik Ibrahimy students who dared to be confident in appearing in front of the class or appearing on the public surface. Keywords: Effectiveness, Hypnosis, Confidence